Simulation of Temperature Control in Growth Room for Tropical Mushroom - Budi I. Setiawan; Diduk A. Wijaya; Leopold O. Netwan (Jurnal Keteknikan Pertanian, 2001)
Optimum growth of tropical mushrooms depend on the ambient environment. In general, mushrooms prefer low air temperature and high air humidity. The growers use closed rooms to maintain favorable conditions. Recently, use of refrigerator is of interest to maintain the favourable conditions under hot and humid climate conditions. This study is attempting to apply control mechanism in maintaining theambient temperature favorable for mushroom growth. A simple heat transfer equation was used to describe changes of temperature inside the growth chamber. This equation was then coupled with a fuzzy logic control to actuate a refrigerator at a suitable length of time. Three temperature condition (16, 19 and 21 O C ) were set as set points. The results show the developed technique was capable to maintain the temperature inside the growth room even though under the influence of a highly fluctuating ambient temperature. This technique was alsoresponsive and reliable in facing immediate disturbances, and showed a realistic requirement of cooling energy.